2019
DOI: 10.3390/ma12193096
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tool Rake Surface Geometry on the Hard Turning Process of AISI52100 Hardened Steel

Abstract: The hard turning process has been widely used in the field of hard material precision machining because of its high efficiency, low processing residual stress, and low environmental pollution. Due to its undesirably processing quality, it is still not a substitute for traditional grinding, so many studies have reported that the process has been optimized. However, there has been little research on the geometry optimization of hard cutting tools, which have a great influence on the traditional machining process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A number of projects have compared the cutting performance of wiper and conventional inserts based on experimental work [12] or finite element simulation [32,33]. Wiper inserts produced a noticeable improvement in achievable surface quality compared with conventional insert [34], revealing the possibility of achieving smoother surfaces at higher feed rates.…”
Section: Introductionmentioning
confidence: 99%
“…A number of projects have compared the cutting performance of wiper and conventional inserts based on experimental work [12] or finite element simulation [32,33]. Wiper inserts produced a noticeable improvement in achievable surface quality compared with conventional insert [34], revealing the possibility of achieving smoother surfaces at higher feed rates.…”
Section: Introductionmentioning
confidence: 99%
“…ε and temperature T. Appropriate material parameters A, B, C, n, and m are listed in Table 1. As the cropping of long metal bars is the first process before forging, the bar material has not yet undergone hardening and tempering, and thus, the strength and hardness are not so high [19].…”
Section: Details Of the Fe Modelmentioning
confidence: 99%
“…Currently, the 1020 and 1045 steel bars with a diameter less than 50 cm are usually cropped by traditional shearing methods, which is highly efficient but causes obvious draw-in distortion. AISI 52100 and 304 steel are typical hard-to-cut steels; the former has high strength [19], and the latter has a high fracture toughness (J IC > 150 kJ/m 2 ) and good ductility [20]. Both types are usually cropped by sawing or the hot-shearing method.…”
Section: Introductionmentioning
confidence: 99%
“…e authors found that an increase in cuttingedge radius reduced TW. Xu et al studied the hard machining of AISI 52100 steel and found that changing tool rake surface geometry significantly reduced cutting temperatures, CF, and residual stresses, compared to the flat tool [15]. However, it also lowered the strength of the cutting edge.…”
Section: Introductionmentioning
confidence: 99%